2018
DOI: 10.2196/10285
|View full text |Cite
|
Sign up to set email alerts
|

Proposing an Ecosystem of Digital Health Solutions for Teens With Chronic Conditions Transitioning to Self-Management and Independence: Exploratory Qualitative Study

Abstract: BackgroundChronic disease management is critical to quality of life for both teen patients with chronic conditions and their caregivers. However, current literature is largely limited to a specific digital health tool, method, or approach to manage a specific disease. Guiding principles on how to use digital tools to support the transition to independence are rare. Considering the physiological, psychological, and environmental changes that teens experience, the issues surrounding the transition to independenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Voice-enabled technology can be leveraged to more accurately report medication compliance, event documentation, and care coaching. In line with that, our previous study demonstrated that voice interactive technologies are expected to promote adherence in health tracking and increase adoption of communication technologies for care management among caregivers and CSHCN [19]. Toward the effort to reduce the adoption problem, we offer an alternative method to mostly manual and error-prone methods in home care, such as delayed event note taking.…”
Section: Long-term Adoption Problem For Health Care Appsmentioning
confidence: 58%
“…Voice-enabled technology can be leveraged to more accurately report medication compliance, event documentation, and care coaching. In line with that, our previous study demonstrated that voice interactive technologies are expected to promote adherence in health tracking and increase adoption of communication technologies for care management among caregivers and CSHCN [19]. Toward the effort to reduce the adoption problem, we offer an alternative method to mostly manual and error-prone methods in home care, such as delayed event note taking.…”
Section: Long-term Adoption Problem For Health Care Appsmentioning
confidence: 58%
“…Gaps in education on health care transitions exist at all levels of medical education [ 44 ], and providers often express concerns about the lack of knowledge on transitioning care for youth with special health care needs [ 45 , 46 ]. Furthermore, youths transitioning from pediatric to adult care also want access to medical education on health care transitions [ 47 ], which can be provided through the tool. There is also a need to provide information on health care transitions among youth with special health care needs to adult providers, who may lack knowledge of the process [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…We plan to interview non–English-speaking caregivers to understand their needs in medical communications, their challenges in using a traditional patient portal, and how a translation app could be seamlessly integrated into the existing channels of communication with their child’s care team. Our previous user-centered research has been successfully implemented [ 15 ], funded (eg, Challenges of the Health Resources and Service Administration’s Maternal and Child Health Bureau), and supported in complex care [ 16 , 17 ]. We will follow a similar strategy to engage end users and community members with our multidisciplinary stakeholder team.…”
Section: Methodsmentioning
confidence: 99%